P006 Probiotics treatment in Crohn's disease: A systematic review and meta-analysis of randomized clinical trial. (July 2019) - Muhammed, Elfaituri; Alkomos Mina, Fransawy; Ammar, Kalo; Nguyen Thi Linh, Hue; Abdulmoate, Alshareef; Mai, Nhu Y.; Nada, Gaballa; Tran, Loc; Bisher, Sawaf; Saed, Enabi; Sherihan E., Galal; Tarek, Ahmed; et al.
Abstract : BACKGROUND: Crohn's disease (CD), a subtype of inflammatory bowel disease (IBD) is chronic idiopathic, relapsing nonspecific inflammatory characterized by transmural inflammation can involve any element of the gastrointestinal tract, although its etiology is unclear yet, the recent studies have shown the associations between the alteration of gut microbiota and CD, furthermore, several studies suggest using probiotic, prebiotic, and synbiotic agents to manipulate the gut microbiota in the management of Crohn's disease. This study aims to bring together the evidence available on the clinical effect of probiotics in Crohn's disease patients. METHODS: To identify all relevant studies, PubMed, MEDLINE, Scopus, Web of Science, and other databases were searched. Randomized clinical trials (RCTs) compared probiotic treatment with placebo were included in this meta-analysis. Primary outcomes were clinical remission and maintenance of remission. Secondary outcomes were adverse events, relapse rate, and endoscopic recurrence rate. RESULTS: Eight randomized clinical trials (RCTs) studies were included for meta-analysis. In the probiotic group, there was no significant difference in term of clinical remission compared to placebo, with an odds ratio of 0.89 (95% CI, 0.33–2.35; P > 0.05). Also, there was no significant difference in terms of adverse events rate between the 2 groups with 62 out of 162 (38.2%) in the probiotic group compared with 59 out of 162 (36.4%) in placebo groups; odds ratio 1.08 (95% CI, 0.08–1.78; P > 0.05). On the other hand, there was no significant difference in terms of relapse rate between 2 groups with 52 out of 124 (41.9%) in the probiotic group compared with 52 out of 121 (42.9%) in placebo groups; odds ratio 0.99 (95% CI, 0.58–1.69; P > 0.5). Regarding endoscopic recurrence rate, there was no significant difference in 2 groups of patients who underwent postoperative follow-up with 76 out of 137 (55.4%) in the probiotic group compared with 88 out 147 (59.8%) in placebo groups; odds ratio 0.86 (95% CI, 0.52–1.42; P > 0.05). CONCLUSION(S): Probiotic is potentially useful in Crohn's disease management. However, it appears to be effective for induction of remission, but with no significant major short-term benefits compared to the placebo group. Finally, there remain many unanswered questions that require further studies before probiotic can be considered for use in the treatment of Crohn's disease.